Autonomous shooting at middle size space debris objects from space-based APT laser systems. (February 2017) - Gambi, J.M.; García del Pino, M.L.
Abstract: This paper is motivated by the need of removing middle size space debris objects. It deals with the problem of increasing the pointing accuracy while shooting at these objects by means of autonomous space-based APT systems endowed with very narrow laser beams. It is shown that shooting at these objects with these systems is the one single ballistic problem that becomes singular in space. This means that the shooting direction that is to be implemented by any of these systems to reach an object at a given instant can only be hopefully implemented after the object has been previously reached. Thus, the problem becomes backwards recurrent with no end for any object–system configuration, except when the LOS direction remains constant for some period of time. It is also shown that the implementation of the point-ahead angles from the data acquired prior to the respective shootings is essential to keep accuracy. In fact, one single omission during the action may cause errors larger than the size of the objects. As a consequence, we find that there is only one way for an autonomous system to minimize the pointing errors: any shooting sequence to any of these objects must be started when the transverse component of the relative velocity of the object with respect to the system is zero (actually, as close to zero as possible). Abstract : Highlights: The problem of shooting at middle size space debris objects from autonomous APT systems is solved. The problem is backwards recurrent in determining the pointing and LOS directions. To keep tracking accuracy, the implementation of point-ahead angles is essential.